2021
DOI: 10.4048/jbc.2021.24.e55
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Diagnosis and Surgery of Breast Cancer: A Multi-Institutional Study

Abstract: Purpose The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the rates of screening, case identification, and referral for cancer diagnosis. We investigated the diagnosis and surgery status of breast cancer before and after the COVID-19 pandemic at a multi-institutional level. Methods We collected breast cancer data from the clinical data warehouse which contained the medical records of patients from six academic institutions in South Korea. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…However, multiple studies have reported that since the emergence of COVID-19, there have been considerable reductions in cancer screening, diagnostic services, endoscopic procedures, and screening-related tests such as biopsies and cervical cytology 3 8 . Similarly, in South Korea, the overall national cancer screening rate was reduced by 6.4% (55.6% in 2019 and 49.2% in 2020) 9 and breast cancer diagnoses were reduced by 9.9% in 2020 10 .…”
Section: Introductionmentioning
confidence: 95%
“…While the shortened 2ww time and increased cancer diagnosis in this study may help ease patients and public anxiety, the COVID-19 pandemic and its restrictions are associated with profound short- and long-term consequences for the patients, hospital organizations, and clinicians. It was anticipated that the reduced 2ww referral rate and breast cancer diagnosis would be followed by a surge in the 2ww referrals and advanced breast cancers after the pandemics [ 18 , 25 ]. It was also predicted that cancer mortality, including breast cancers, will worsen after the pandemic [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also predicted that cancer mortality, including breast cancers, will worsen after the pandemic [ 8 , 10 ]. Some studies have shown a rebound in the 2ww referral [ 12 , 16 , 17 , 26 ] and breast cancer diagnosis rates [ 16 , 25 ] and predicted a shift in breast cancer diagnosis from early to advanced stages following the COVID-19 pandemic [ 18 , 25 ]. Several specialist breast services have implemented telephone consultations and virtual meetings during the COVID-19 pandemic [ 27 ].…”
Section: Discussionmentioning
confidence: 99%